Identifying Saharan dust driven export of biogenic material in the ultraoligotrophic eastern Mediterranean Sea - van Boxtel, Anouk P. E.; Stuut, Jan-Berend W.; Peterse, Francien (Frontiers in Marine Science, 2025)
To assess the effects of dust deposition on the strength of the biological pump in the Mediterranean Sea by acting as fertilizer and/or ballasting agent, we analyzed fluxes of mineral dust, particulate organic carbon (POC) and inorganic carbon (PIC), and source-specific lipid biomarkers (i.e., higher plant-derived long-chain fatty acids and phytoplankton-derived alkenones, C30 1,15 diols, and sterols) in sinking particles. Sinking particles were collected at ten-day intervals by a sediment-trap mooring deployed in the Ionian Basin from April 2017 to May 2018 at 2340 m water depth. High POC fluxes occur during summer, when surface ocean primary production is lowest due to thermal stratification. Notably, these high POC fluxes coincide with pulses of substantial dust deposition, suggesting that POC export is primarily driven by dust deposition and subsequent ballasting. However, the lipid composition, and thereby that of the phytoplankton community, differs between dust events. (Seasonal) variations in the properties of the deposited dust, presumably associated with its provenance, likely control the effect of dust deposition on phytoplankton response and export in the Ionian Basin. Although POC export is associated with dust deposition, the net effect of dust deposition on the biological pump is more ambiguous as not all dust events are associated with an increase in POC export, and most dust events are also associated with PIC export that has a counteracting effect on the biological pump. Multi-year time series of dust deposition and biogenic export are required to validate the seasonal variations in dust-driven export of biogenic material observed here, and to account for effects of interannual variations in dust fluxes and phytoplankton production on the strength of the biological pump.